The last ever after - Chainani, Soman; Bruno, Iacopo (2015)
Everything old is new again as Sophie and Agatha fight the past as well as the present to find the perfect end to their fairy tale. Once best friends, now enemies, Sophie and Agatha thought their ending was sealed when they went their separate ways. Agatha was whisked back to Gavaldon with Tedros, and Sophie stayed behind with the beautiful young School Master. But as they settle into their new lives, their story begs to be rewritten, and this time, theirs isn't the only one. With the girls apart, Evil has taken over and the villains of the past have come back with a vengeance. Not only do they want a second chance at their fairy tales, but they mean to transform the old world of Good and Evil into a new dark realm with Sophie as its Queen. Only Agatha and Tedros stand in the way of Evil's deadly reign -- and the Last Ever After of all.
Ages 8-12.
Keywords: Good and evil -- Juvenile fiction; Good and evil -- Fiction; Fantasy; Best friends; Friendship; Good and evil; Schools; Fiction; Juvenile works; Fantasy fiction